The Test Effect of Glucose Tolerance of Green Apple (Mallus sylvestris Mill.) Juice on Male White Mice - Mevy Trisna; Renatalia Fika; Dewi Novita; Budi Setiawan; Wenni (Science Midwifery, 2022)
Diabetes Mellitus or diabetes is a disease characterized by an increase in blood sugar levels beyond normal limits due to disruption of carbohydrate metabolism due to a deficiency of the insulin hormone caused by impaired pancreatic function. Glucose tolerance is disturbed when a person's blood sugar level on the glucose tolerance test is above normal but not high enough. Green Apple (Mallus sylvestris Mill.) Glucose Tolerance Test. Against White Male Mice orally by measuring mice's blood sugar levels every 30 minutes for 3 hours at a dose of 1.12 g; 2.24 g; and 4.48 g. The study's results using the oral glucose tolerance test method showed that the glucose tolerance effect of green apple juice at a dose of 1.12 g averaged blood sugar levels from 160.33 mg/dl to 89.33 mg/dl, at a dose of 2.24 g. – average blood sugar level from 204.67 mg/dl to 122.33 mg/dl and a dose of 4.48 g average blood sugar level from 329.67 mg/dl to 175.00 mg/dl. At a dose of 4.48 g, it can provide a faster effect on lowering the glucose levels of the test animals from statistical testing utilizing the T-test obtained tcount ≤ ttable means that there is no significant difference between the test substance group and the normal group.